Cytokine and cytokine receptor genes of the adaptive immune response are differentially associated with breast cancer risk in American women of African and European ancestry. Issue 6 (8th October 2013) - Quan, Lei; Gong, Zhihong; Yao, Song; Bandera, Elisa V.; Zirpoli, Gary; Hwang, Helena; Roberts, Michelle; Ciupak, Gregory; Davis, Warren; Sucheston, Lara; Pawlish, Karen; Bovbjerg, Dana H.; et al.
<x xml:space="preserve">Abstract</x> Disparities in breast cancer biology are evident between American women of African ancestry (AA) and European ancestry (EA) and may be due, in part, to differences in immune function. To assess the potential role of constitutional host immunity on breast carcinogenesis, we tested associations between breast cancer risk and 47 single nucleotide polymorphisms (SNPs) in 26 cytokine‐related genes of the adaptive immune system using 650 EA (n = 335 cases) and 864 AA (n = 458 cases) women from the Women's Circle of Health Study (WCHS). With additional participant accrual to the WCHS, promising SNPs from the initial analysis were evaluated in a larger sample size (1, 307 EAs and 1, 365 AAs). Multivariate logistic regression found SNPs in genes important for T helper type 1 (Th1) immunity (IFNGR2 rs1059293, IL15RA rs2296135, LTA rs1041981), Th2 immunity (IL4R rs1801275), and T regulatory cell‐mediated immunosuppression (TGFB1 rs1800469) associated with breast cancer risk, mainly among AAs. The combined effect of these five SNPs was highly significant among AAs (P‐trend = 0.0005). When stratified by estrogen receptor (ER) status, LTA rs1041981 was associated with ER‐positive breast cancers among EAs and marginally among AAs. Only among AA women, IL15 rs10833 and IL15RA rs2296135 were associated with ER‐positive tumors, and IL12RB1 rs375947, IL15 rs10833 and TGFB1 rs1800469 were associated with ER‐negative tumors. Our study systematically identified genetic variants in the adaptive immune response pathway associated with breast cancer risk, which appears to differ by ancestry groups, menopausal status and ER status.